2014
DOI: 10.1016/j.bbrc.2014.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Insights into miRNA regulation of the human glycome

Abstract: Glycosylation is an intricate process requiring the coordinated action of multiple proteins, including glycosyltransferases, glycosidases, sugar nucleotide transporters and trafficking proteins. Work by several groups points to a role for microRNA (miRNA) in controlling the levels of specific glycosyltransferases involved in cancer, neural migration and osteoblast formation. Recent work in our laboratory suggests that miRNA are a principal regulator of the glycome, translating genomic information into the glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Recent work by our laboratory has shown miRNAs are major regulators of the glycome (79). To date 10 human glycogenes have been validated as miRNA targets in the literature (7, 8).…”
mentioning
confidence: 99%
“…Recent work by our laboratory has shown miRNAs are major regulators of the glycome (79). To date 10 human glycogenes have been validated as miRNA targets in the literature (7, 8).…”
mentioning
confidence: 99%
“…Although OGT was not regulated by miR-424 in MCF-7, the miRNA-dependent regulation of OGT is of special interest. Previous analysis of the 3Ј-UTR of OGT revealed that it is one of the most highly regulated glycogenes (41). O-GlcNAc, the epitope controlled by this enzyme, is involved in cell proliferation (42,43), consistent with targeting by miR-424.…”
Section: Discussionmentioning
confidence: 93%
“…Mahal and co-workers (51) revealed critical nodes in the global glycosylation network accessible to microRNA regulation, providing an miRNA regulatory map for glycogenes both in the N-linked and O-linked glycosylation pathways, among which galnt1, galnt7, fut4, fut8, and manea are predicted to be highly regulated genes. Changes in microRNA may underlie the altered glycosylation observed in dynamic processes in cancer phenotypes (52). Bernardi et al (53) reported that fucosyltransferase 8 (FUT8), catalyzing core fucosylation, was regulated by miR-122 and miR-34a during hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%